A Roadmap for Research Culture and Digital Transformation in Indonesian Student Organizations: a Case of PP HIMA PERSIS (2025–2028) - Fadhlurrohman, Hafidh; Sawalludin, Faizal Rizqi; Surizkika, Aldi (Journal of English Language and Education, 2026)
This article offers a roadmap for revitalizing research culture and digital transformation for PP HIMA PERSIS for the 2025–2028 period, emphasizing that the main challenge is not merely a lack of individual skills or platforms, but rather the weak institutionalization of knowledge practices. Based on organizational learning theory and institutional perspectives, research is understood as an organizational capability that requires stable routines, output standards, quality assurance mechanisms, and documented organizational memory so that knowledge is cumulative and can be audited across management generations. Digital transformation in this framework is positioned as a governance infrastructure—repositories, revision trails, decision documentation, and workflow standardization—that enables organizations to "remember," make corrections, and improve work quality continuously, not just accelerate publication and communication. Thus, the article emphasizes the mutually reinforcing relationship between research and digitization: research requires strict governance, while governance becomes realistic when supported by a minimal but scalable digital stack. The final output is an implementable framework that directs changes in values into norms, norms into practices, and practices into systems without stifling the critical thinking that is the source of intellectual energy for HIMA PERSIS cadres in Indonesia.